2020
DOI: 10.1093/abbs/gmaa028
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal piRNA profiling revealed unique circulating piRNA signatures of cholangiocarcinoma and gallbladder carcinoma

Abstract: Cholangiocarcinoma (CCA) and gallbladder carcinoma (GBC) are biliary tract cancers with poor five-year survival and high recurrence rates. Both CCA and GBC patients suffer from lack of circulating diagnostic biomarkers at the early stage. Extracellular vesicles, especially exosomes, have been emerged as promising diagnostic sources for cancers due to easy and quick accessibility. Hence, identification of exosomal biomarkers provides a novel strategy for CCA and GBC diagnosis. Here, five CCA patients and four G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 29 publications
0
49
0
Order By: Relevance
“…202 Two other preclinical studies found differentially expressed extracellular vesicle RNAs between patients with cholangiocarcinoma and healthy controls. 203,204 To conclude, several subpopulations of extracellular vesicles have the potential to become very useful tools to differentiate cholangiocarcinoma from primary sclerosing cholangitis and other tumours. The use of demanding techniques to measure extracellular vesicles would likely not be a limitation in this setting since these situations are not common and patients are usually referred to expert centres.…”
Section: Primary Sclerosing Cholangitis and Cholangiocarcinomamentioning
confidence: 99%
“…202 Two other preclinical studies found differentially expressed extracellular vesicle RNAs between patients with cholangiocarcinoma and healthy controls. 203,204 To conclude, several subpopulations of extracellular vesicles have the potential to become very useful tools to differentiate cholangiocarcinoma from primary sclerosing cholangitis and other tumours. The use of demanding techniques to measure extracellular vesicles would likely not be a limitation in this setting since these situations are not common and patients are usually referred to expert centres.…”
Section: Primary Sclerosing Cholangitis and Cholangiocarcinomamentioning
confidence: 99%
“…37 In addition, piR-10506469 were found to be significantly increased in the exosomes of plasma from both cholangiocarcinoma and gallbladder carcinoma patients, indicating it may be serve as the potential cancer biomarker. 38 Exosomes secreted from tumour cells may contain several piRNAs originated from cells, 39 which may be aberrantly expressed in tumour cells. Whether serum exosomal piRNAs are biomarkers for other cancers deserves further study.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, piR-10506469 was further validated in blood samples from a large cohort of patients with GBC and CCA as being significantly increased compared to healthy controls. The same analysis of patients that underwent resection therapy showed that this specific piRNA decreases after tumor removal, together with piR-20548188 [55].…”
Section: Exosomal Loading Of Rare Rnas In Billary Tract Tumors and Thmentioning
confidence: 91%